2017
DOI: 10.1038/cgt.2016.80
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic vaccination based on side population cells transduced by the granulocyte–macrophage colony-stimulating factor gene elicits potent antitumor immunity

Abstract: Among cancer immunotherapies, granulocyte-macrophage colony-stimulating factor (GM-CSF) gene-transduced tumor cell vaccine (GVAX) therapies appear promising and have been shown to be safe and effective in multiple clinical trials. However, the antitumor efficacies of GVAX therapy alone are in some cases limited. Here we showed that GVAX therapy targeting cancer stem cells (CSCs) substantially suppressed tumor development in syngeneic immunocompetent mice recapitulating normal immune systems. CSCs were isolated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…Another approach is based on the use of adjuvants to boost the immune response. Among these, GM-CSF used in vaccines as GVAX (253) and STINGVAX (254) and, even TLR agonists (255), may be more effective for cell maturation. Other adjuvants could be listed, as for example, aluminum salts (256) (an inflammasome activator), and montanide (257) (an equivalent to incomplete Freund's adjuvant).…”
Section: Strategies To Improve the Clinical Effectiveness Of Mo-dc-bamentioning
confidence: 99%
“…Another approach is based on the use of adjuvants to boost the immune response. Among these, GM-CSF used in vaccines as GVAX (253) and STINGVAX (254) and, even TLR agonists (255), may be more effective for cell maturation. Other adjuvants could be listed, as for example, aluminum salts (256) (an inflammasome activator), and montanide (257) (an equivalent to incomplete Freund's adjuvant).…”
Section: Strategies To Improve the Clinical Effectiveness Of Mo-dc-bamentioning
confidence: 99%
“…GVAX is a vaccine platform comprising of irradiated allogeneic or autologous tumor cells engineered to secrete GM-CSF which can illicit T cell immunity against TAAs to improve median survival in patients [49]. The concept of leveraging cancer stem cells for the formulation of GVAX platform has been validated in murine models of breast cancer [50]. GM-CSF secreting, STINGVAX, has proven to be a promising anti-tumorigenic vaccine in murine studies [40].…”
Section: Emerging Vaccine Adjuvantsmentioning
confidence: 99%
“…In fact, if the phenotypic switching mechanisms will be fully understood, it might be possible to target with a vaccine all the tumor cells in a way that does not allow them to switch. In a recent interesting paper, the authors showed that using a gene-transduced tumor cell vaccine therapy targeting CSCs they found a substantially suppression in syngenic immunocompetent mice recapitulating normal immune systems [72]. This system seems very interesting to induce potent tumor-specific antitumor immunity [72].…”
Section: Cscs Metastasis and The Immune Systemmentioning
confidence: 99%
“…In a recent interesting paper, the authors showed that using a gene-transduced tumor cell vaccine therapy targeting CSCs they found a substantially suppression in syngenic immunocompetent mice recapitulating normal immune systems [72]. This system seems very interesting to induce potent tumor-specific antitumor immunity [72]. Moreover, considering the plasticity of both the tumor cells and the plasticity of immune system, the interaction between the two compartment might be protumorigenic or antitumorigenic.…”
Section: Cscs Metastasis and The Immune Systemmentioning
confidence: 99%